New perspectives on Microsoft Office PowerPoint 2003. Introductory - Zimmerman, Beverly B. (Thomson Course Technology, 2006)
Part of the New Perspectives series, this text offers a case-based, problem-solving approach and innovative technology for meaningful learning the new features of this latest version of Microsoft PowerPoint 2003